2017
DOI: 10.1016/j.anl.2016.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in knowledge regarding the head and neck manifestations of IgG4-related disease

Abstract: IgG4-related disease (IgG4-RD) is a chronic inflammatory disorder, characterized by elevated serum IgG4 levels as well as abundant infiltration of IgG4-positive plasmacytes and fibrosis in various organs, including the head and neck region. In particular, the salivary glands, orbit, and thyroid are common sites of disease involvement. IgG4-RD is diagnosed based on various clinical, serological, and histopathological findings, none of which are pathognomonic. Hence, various differential diagnoses, which exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
104
0
22

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(126 citation statements)
references
References 101 publications
0
104
0
22
Order By: Relevance
“…In addition, patients with abundant IgG4‐positive plasma cell infiltration into the labial salivary gland tissue have a tendency to show FDG uptake by the PG . Therefore, relationships between increased uptake of FDG by the PG and IgG4‐SS disease activity in all major and minor salivary glands are considered to be present . In the present study, FDG uptake by the PG was observed in 35% patients, and their serum IgG4 levels and sIL‐2R were significantly higher (data not shown).…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…In addition, patients with abundant IgG4‐positive plasma cell infiltration into the labial salivary gland tissue have a tendency to show FDG uptake by the PG . Therefore, relationships between increased uptake of FDG by the PG and IgG4‐SS disease activity in all major and minor salivary glands are considered to be present . In the present study, FDG uptake by the PG was observed in 35% patients, and their serum IgG4 levels and sIL‐2R were significantly higher (data not shown).…”
Section: Discussionmentioning
confidence: 46%
“…Immunoglobulin G4‐related disease (IgG4‐RD) is a systemic immune‐mediated disease characterized by elevated serum immunoglobulin G4 (IgG4) levels, dense lymphoplasmacytic infiltration, and fibrosis of the affected organs . IgG4‐RD, which is more common than previously suspected, can affect various organs, but the pathogenesis remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histopathology is the hallmark for diagnosis of IgG4 RD and subsequently EAF 10. It is imperative not to rely on measurement of serum IgG4 as it is not specific for IgG4 RD and has a low positive predictive value 11.…”
Section: Discussionmentioning
confidence: 99%
“…Лечение гипотиреоза на фоне АИТ сводится в основном к использованию заместительной тера-пии тиреоидными гормонами (ТГ) в случае его мани-фестации [4,7]. Однако по современным представле-ниям ТГ отводят роль антигенов в патогенезе ауто-иммунного воспаления ЩЖ [5,8,9], из чего следует, что заместительная терапия в этих случаях может поддерживать персистенцию аутоиммунного про-цесса, в том числе при IgG4-обусловленном тирео-идите, когда наиболее важное значение приобретает взаимодействие В-и Т-клеток с клетками врожден-ного иммунитета [1,4,5,10]. АИT относится к за-болеваниям, при котором аутоиммунное воспаление опосредовано прежде всего Т-клетками, а точная роль В-клеток в его патогенезе также остается до сих пор неясной [2][3][4].…”
Section: актуальностьunclassified